The student involvement in view of mathematical problem solving ability - Fitra, Rifka Yani; Munzir, Said; Ansari, Bansu Irianto (International Journal of Trends in Mathematics Education Research, 2023)
Students are still less involved in the teaching and learning process in class in mathematics. Lack of student involvement resulted in students' problem-solving abilities being weak. Constraints faced by students included difficulties in building plans, errors in operationalizing plans, and wrong conclusions. The purpose of this study was to determine student involvement in terms of students' mathematical problem-solving abilities in mathematics. This study uses a descriptive qualitative research approach. The subjects in this study were 12 students of class XII IPA-2 at MAN 4 North Aceh. Data collection techniques used in this study were observation, interviews and documentation. Data analysis techniques using data reduction, data presentation, and drawing conclusions. The results of the study show that in general high problem-solving abilities are also accompanied by high involvement, and vice versa. However, students in the high group have not been involved in finding answers, exploring variations and sorting information, and making inductions. Medium group students have not been involved in classifying, exploring variations and expressing in their own words and finding answers, sorting information and making inductions. Meanwhile, students in the low group were only able to clarify, associate and generalize, use previous knowledge, create mathematical objects and provide examples.